Genetic polymorphisms at candidate genes affecting fat content and fatty acid composition in Modicana cows: effects on milk production traits in different feeding systems. (5th November 2018) - Valenti, B.; Criscione, A.; Moltisanti, V.; Bordonaro, S.; De Angelis, A.; Marletta, D.; Di Paola, F.; Avondo, M.
Abstract : Feeding greatly affects milk yield and composition. The research is highlighting the potential of genetic polymorphism at some loci to affect milk yield and quality traits. These loci can be up/down regulated depending on the production environment; therefore, we hypothesized that milk yield and composition could differ when cows with different genotype at SCD, DGAT1 and ABCG2 loci are reared in different feeding systems. The polymorphisms of SCD, DGAT1 and ABCG2 genes were investigated in Modicana breed. In all, three polymorphic sites, responsible for the genetic variation of quantitative trait loci and therefore defined quantitative trait nucleotides, were genotyped: the transition g.10329C>T in 5 th exon determines a substitution p.A293V in the SCD, the dinucleotide mutation g.10433-10434AA>GC in 8 th exon responsible for p.K232A substitution in the DGAT1 and the transition g.62569A>C in the 14 th exon responsible for p.Y581S substitution in the ABCG2 gene. In the sample of 165 Modicana cows, SCD and DGAT1 genes resulted polymorphic; the alleles g.10329T and g.10433 - 10434GC were the most frequent in SCD and DGAT1 (0.73 and 0.91) respectively, whereas ABCG2 locus was monomorphic for allele A (p.581Y). Sequencing analysis was carried out on 14 samples with different genotypes to confirm the results of the PCR-RFLP protocols. Based on the genotypes at SCD locus, 47 Modicana cows were selected for the nutritional trial: 24 cows in a semi-intensive farm, with 2 h/day grazing on natural pasture, and 23 cows in an extensive farm, with 8 h/day grazing on natural pasture. Monthly, milk yield and composition were evaluated and individual milk samples were analyzed for fatty acids composition by gas chromatography. No differences in milk yield, fat, protein, lactose, casein and urea were associated to SCD genotype. Feeding systems affected milk yield and composition. No significant genotype×feeding system interaction was observed for milk yield and composition. Fatty acids composition was significantly affected only by the feeding system. Significant interactions were found between SCD genotype and feeding system for six fatty acids: 4:0, 6:0, 8:0, 10:0, 12:0 and t 11 18:1. We concluded that the feeding system was the factor that mostly affected milk production and composition; moreover, our results do not confirm what reported in literature as regard the effect of the SCD polymorphism on milk fatty acid composition. The high amount of pasture seemed to have resized the SCD polymorphism effects because of the different fatty acids composition of the diet.